Identification Ways Of Working Of Students' High School Pekanbaru In Chemistry Learning - Tissa Indah; Asyti Febliza (JPP (Jurnal Pendidikan dan Pembelajaran), 2023)
The background of this research is the absence of an assessment of communication and collaboration skills of students in overall chemistry learning when learning shifts from home to face-to-face limited during the pandemic. This study aims to show the value of the working skills of high school students in learning chemistry in Pekanbaru. The research subjects involved were 379 students from high school in Pekanbaru. This research is survey research that uses a quantitative descriptive approach. Data collection methods used are questionnaires and interviews. The instruments used are self-assessment, peer assessment, and interview guidelines. The data analysis technique used quantitative analysis. The results showed that the average value of working skills (communication and collaboration) in chemistry learning in Pekanbaru had the same value. This value is 62% which is classified as a strong category. The implications of this research are expected to be useful as teacher quality in core competencies KI-2 and KI-4 in chemistry learning during the pandemic. In addition, this research needs to be carried out to identify students' communication and collaboration skills so that they can be used as reflective material for teachers to design learning that directs students to have communication and collaboration skills that are very much needed in today's 21st century